Botanical Insecticide Based on Annona mucosa Agro-industrial Waste as an Alternative to Manage Lepidopteran Soybean Defoliators - de Souza, Camila Moreira [UNESP] (2024)
Fruit processing waste from Annona mucosa Jacq. (Annonaceae) is an interesting source of biomass for development of ecofriendly botanical insecticides. Here, we evaluated the lethal and sublethal effects of the ethanolic extract prepared from seeds of A. mucosa (ESAM; major component = acetogenin bis-tetrahydrofuran rolliniastatin-1) against Chrysodeixis includens (Walker) and Anticarsia gemmatalis Hübner, two major defoliators of soybean crops. In the initial trial, ESAM showed activity comparable or superior to our positive control (Azamax® 1.2 EC, at recommended rate). The larvae of C. includes survived at higher levels than A. gemmatalis when exposed to ESAM. To cause mortality of 50 and 90% of the population of A. gemmatalis, 66.91 and 288.36 mg kg−1 was needed, respectively, whereas, for C. includens, 452.38 and 885.70 mg kg−1 were required, respectively. In addition, 27.23 and 51.01 h were needed to cause 50% of mortality against A. gemmatalis and C. includens, respectively. Under semi-field conditions (greenhouse), the aqueous emulsion of ESAM (pre-commercial formulation) and Azamax® 1.2 EC caused larval mortality above 95% for both pest species exposed to treated soybean plants. These results show that A. mucosa processing waste can be a source of promising botanical insecticides for the management of C. includens and A. gemmatalis, which are the main economically lepidopteran defoliators of soybean crops.